2005
DOI: 10.1093/jxb/eri303
|View full text |Cite
|
Sign up to set email alerts
|

Root-ABA1, a major constitutive QTL, affects maize root architecture and leaf ABA concentration at different water regimes

Abstract: Near-isogenic hybrids (NIHs), developed from crossing maize (Zea mays L.) backcross-derived lines (BDLs) differing for the parental alleles at a major QTL for leaf ABA concentration (L-ABA), were field-tested for 2 years under well-watered and water-stressed conditions. Differences among NIHs for L-ABA and other morpho-physiological traits were not affected by water regimes. On average, the QTL allele for high L-ABA markedly reduced stomatal conductance and root lodging. To elucidate the effects of the QTL on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 164 publications
(103 citation statements)
references
References 22 publications
4
94
1
3
Order By: Relevance
“…6H). It was found to constitutively affect leaf ABA content (Giuliani et al, 2005), consistent with the fact that a gene coding for a zeaxanthin epoxidase involved in ABA biosynthesis was identified in the region of the QTL (Supplemental Table S7). This could explain the inversion of allelic effects of this QTL in WW and WD scenarios because high ABA can cause reduction in growth in WW while maintaining growth in WD Tardieu, 2012).…”
Section: Genomic Regions Controlling Grain Yield Displayed Scenario-dsupporting
confidence: 73%
“…6H). It was found to constitutively affect leaf ABA content (Giuliani et al, 2005), consistent with the fact that a gene coding for a zeaxanthin epoxidase involved in ABA biosynthesis was identified in the region of the QTL (Supplemental Table S7). This could explain the inversion of allelic effects of this QTL in WW and WD scenarios because high ABA can cause reduction in growth in WW while maintaining growth in WD Tardieu, 2012).…”
Section: Genomic Regions Controlling Grain Yield Displayed Scenario-dsupporting
confidence: 73%
“…In rice, following the identification of four major QTLs influencing root traits (Courtois et al, 2000), markerassisted backcrossing (MABC) was used to introgress the alleles for greater root length from Azucena into Kalinga III, an upland variety (Steele et al, 2006(Steele et al, , 2007. In maize, a major QTL originally reported for leaf ABA concentration (Tuberosa et al, 1998) was later shown to affect root size and architecture (Giuliani et al, 2005b) and grain yield (Landi et al, 2007). Following its isogenization (Landi et al, 2005), the positional cloning of this QTL is under way at present (S. Salvi, unpublished data).…”
Section: Qtls For Drought Tolerancementioning
confidence: 99%
“…The increase in ABA level reprograms the expression patterns of many genes to regulate water relations through adjustment of cellular osmotic pressure. Furthermore, the increase in ABA level is a central player controlling downstream responses essential for adaptation to different stresses, especially drought (Davies et al, 2002 andGiuliani et al, 2005). These responses include changes in stomatal conductance (closure of stomata), osmolyte accumulation, gene expression, a reduced leaf canopy, deeper root growth and changes in root system architecture (Davies et al, 2002;Giuliani et al, 2005;Lee et al, 2013 andAn et al, 2016).…”
Section: Introductionmentioning
confidence: 99%